A challenge for psychocardiology: Addressing the causes and consequences of patients' perceptions of enduring somatic threat - Edmondson, Donald; Birk, Jeffrey L; Ho, Vivian T; Meli, Laura; Abdalla, Marwah; Kronish, Ian M (The American psychologist, 2018)
The enduring somatic threat (EST) model of posttraumatic stress disorder (PTSD) due to life-threatening medical events suggests that PTSD-like symptoms represent patients' sensitization to cues of ongoing threat in the body. In this article, we review research on the prevalence and consequences of such reactions in cardiovascular disease patients, discuss early tests of the EST model, and then report a new test of the EST model in 143 patients enrolled during their first acute coronary syndrome (ACS; i.e., non-ST elevation myocardial infarction or unstable angina-colloquially, "heart attack"). Invasive coronary revascularization procedures are commonly used to reduce secondary ACS risk and may reduce patients' EST, as revascularized patients often report being "cured." We assessed ACS patients' initial threat perceptions during emergency department (ED) evaluation and followed them for 1 month for PTSD symptoms (specific for ACS, by telephone). We compared PTSD symptoms in participants who were revascularized (n = 65), catheterized but not revascularized (n = 35), and medically managed (n = 43). PTSD symptoms were lower for revascularized versus medically managed participants (B = -5.32, 95% confidence interval [-9.77, -0.87]), t(98.19) = -2.37, p = .020. In a multiple regression model adjusted for clinical and psychosocial covariates, the interaction of threat perception in the ED and ACS management group was significant (greater ED threat predicted greater 1-month PTSD symptoms only in medically managed participants). These findings offer further support for the EST model and suggest that psychological interventions to preempt patients' development of EST should be considered in the hospital. (PsycINFO Database Record (c) 2018 APA, all rights reserved).